Buddhist Environmentalism as Seen through Religious Change - Lin, Nan Kathy (Religions, 2022)
This article considers the disagreement between scholars of Buddhism around whether the tradition is or is not amenable to environmental concerns. It identifies the gap between the two sides as arising from a problem in how historical-critical methods divorce moral concepts from materiality in the study of religious history. This paper considers paticca-sammupada as a central moral concept in Buddhist tradition, one that has indeed changed via translation over the course of Buddhist history. This is the moral concept that leads directly into current environmentalist discourse, in its translation as interdependence. The paper first considers the translation of paticca-sammupada in historical tradition as well as in the hands of environmentalist authors. It then considers why paticca-samuppada as interdependence is a context-appropriate contribution, in settings of industrial political economy heavily directed by an abstract, mathematical concept of capital in connection with the moral concept of unlimited growth. The paper concludes by suggesting that contemporary Buddhist environmentalism be understood as a case of religious change. It concludes that the Buddhist eco-critical position is untenable, in light of processes of change in religious traditions, and suggests that the study of religious history should better account for how it is that religious change occurs.